Influence of Involute Cylindrical Gear Tooth Profile Modification on the Stress of Gear Tooth - Xiao Han; Xinli Xu (Jixie chuandong)
Through the analysis and study of involute gear modification, a new method is applied to modify the gear nonworking surface. And the tooth profile equation of the involute gear nonworking surface is built. According to the equation, the finite element analysis model of different modification parameters is established. The static finite element analysis of the gear is carried out by using the software of Ansys Workbench, the stress cloud diagram of gear tooth root is obtained. Through the contrast between the different amounts of modification, the relationship between the modification amount and the root stress is obtained. The results show that the gear tooth stress distribution can be improved by modifying the gear, the stress of the toot of gear is decreased as the increase of repair parameters.